Perencanaan Bandung Cinema Center Dengan Pendekatan Rekreasi Perkotaan dan Art Deco Pada Bangunan - Harry Miarsono; Herol Herol; Herwadi Sahid (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
The development of world technology is growing rapidly, as well as technological developments in Indonesia. Currently, technology dominates various fields and one of the fields that is heavily affected by technological developments is the world of cinema. The city of Bandung is a city that has a strong historical value with the development of films in Indonesia, starting from 1920 where the premiere of the film was played by indigenous people and aired in the city of Bandung, precisely in the elite cinema which had become the most popular cinema in its mass. In addition, the city of Bandung still requires additional recreational facilities, especially cinemas in each zone of its territory. The identity of Bandung City as the largest Art Deco City in the world is slowly starting to be forgotten along with the popularity of buildings with modern concepts. The planning of this building is expected to reawaken public awareness of the importance of preserving cultural heritage in the city of Bandung and become a building that can revive the film industry that is able to compete globally. Based on some background that became the basis for consideration required additional recreational facilities specifically in the field of film in the city of Bandung. The planning theme for this Bandung Cinema Center is Art Deco Architecture with an Approach to Utilization of Cultural Heritage Areas as a form of building style. So that later it is hoped that the Bandung Cinema Center building will produce an iconic building and can revive the feel of the city of Bandung as the city with the largest number of art deco buildings in the world.